Evaluation of the Use of the POLRI Super App in Online Police Clearance Certificate (SKCK) Applications in Central Kalimantan - Risa Lina; Alfri A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the use of the POLRI SUPER APP in providing online services for obtaining a Police Clearance Certificate (SKCK) at the Central Kalimantan Regional Police and to identify the challenges encountered during its implementation. This research is driven by efforts to transform public services through the implementation of the Electronic-Based Government System (SPBE), which aims to improve the effectiveness, efficiency, and quality of services provided to the community. This study uses a qualitative approach, and data were collected through observation, interviews, and documentation. The study involved staff from the SKCK service and members of the public who used the online SKCK service. The results of the study indicate that the use of the POLRI SUPER APP has facilitated the process of obtaining an SKCK, as the service can be accessed in a more convenient, faster, and efficient manner. The application helps the public register without having to visit the service location beforehand. Nevertheless, its implementation still faces several challenges, such as server issues, difficulties in the account verification process, unstable internet connections, and a lack of understanding among some members of the public regarding the use of digital-based services. In addition, people are still required to visit the service office for verification and document collection, meaning that the benefits of digitalization have not yet been fully realized.